A Case of Acute Calcific Tendinitis of the Hand: An Uncommon Condition that is Easily Overlooked and Misdiagnosed. Issue 5 (September 2015) - Yip, KC; Chan, WL; Luk, MS; Chan, CW
Acute calcific tendinitis of the hand is uncommon, yet it has a high rate of misdiagnosis as it resembles other conditions such as fractures, inflammatory and infectious causes that give rise to pain and swelling in the hand. We present a case of acute calcific tendinitis in a middle age woman affecting the extensor pollicis longus to raise awareness of this uncommon, but easily treatable cause of pain and swelling. This case was first diagnosed as septic arthritis of the interphalangeal joint of the thumb. Correct diagnosis was made after careful review of history, physical examination findings, laboratory results and radiographs. (Hong Kong j. emerg.med. 2015;22:316-319)